Integrating Environmental Sustainability into Islamic Religious Education Curriculum Development - Taisir, Muhammad Taisir; Mohamad Iwan Fitriani; Abdul Quddus (Universitas Islam Negeri (UIN) Mataram, 2024)
This study explores the development of an environmental-based Islamic Religious Education (PAI) curriculum, focusing on the integration of Islamic principles and values into environmental awareness and sustainability practices. The research emphasizes the importance of aligning PAI curriculum objectives with Islamic teachings about nature, human stewardship (khalifah), and environmental responsibility. By utilizing methods such as lectures, discussions, and modeling, the curriculum aims to foster spiritual, social, and environmental piety among students. Key recommendations include the use of appropriate learning media, the promotion of hands-on environmental activities, and continuous assessments to ensure students' understanding and commitment to environmental preservation. The study underscores the need for a holistic approach in Islamic education that nurtures both the spiritual and ecological dimensions of students' character development.